Improve Nepalese mechanization policy: Focus on appropriate-scale and gender equality - CGIAR Research Program on Maize (2020)
MAIZE scientists recommend 3 strategies to promote responsible agricultural mechanization - and that policymakers implement female-targeted farm mechanization programs, to enhance the level of small-scale mechanization in Nepal's hilly regions